Research on Geometric Mappings in Complex Systems Analysis. (29th November 2016) - Cui, Yanyan; Wang, Chaojun; Zhu, Sifeng
Abstract : We mainly discuss the properties of a new subclass of starlike functions, namely, almost starlike functions of complex orderλ, in one and several complex variables. We get the growth and distortion results for almost starlike functions of complex orderλ . By the properties of functions with positive real parts and considering the zero of orderk, we obtain the coefficient estimates for almost starlike functions of complex orderλ onD . We also discuss the invariance of almost starlike mappings of complex orderλ on Reinhardt domains and on the unit ballB in complex Banach spaces. The conclusions contain and generalize some known results.